ISO/IEC 25010-Based Evaluation of a Web-Based Internship Monitoring Information System for Vocational Education - Annas Nur Aziz; Rahmatul Irfan (FKIP - Universitas Riau, 2026)
A web-based internship monitoring information system was developed to address challenges in managing and monitoring student internship activities in vocational education. This study aims to evaluate the quality of the system using the ISO/IEC 25010 software quality model. Unlike previous studies that primarily focused on system development, this research provides a comprehensive software quality evaluation by integrating functional suitability, usability, reliability, and performance efficiency within a single assessment framework. Functional suitability testing involved three expert validators and 55 functional test cases. Usability evaluation was conducted with 45 respondents, consisting of students, supervising teachers, heads of study programs, and industry instructors, using the User Experience Questionnaire (UEQ). Reliability testing employed Web Application Performance Testing (WAPT), while performance efficiency was assessed using Google Lighthouse. The results showed that the system achieved a functional suitability score of 100% and a reliability score of 96.57%. Usability evaluation indicated positive user experience across all dimensions, while performance testing demonstrated acceptable performance for web-based applications. Overall, the findings indicate that the system satisfies key ISO/IEC 25010 quality characteristics and can effectively support internship monitoring activities in vocational education environments.